2011
DOI: 10.1089/ars.2010.3370
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Forkhead Box O1 from the Concept to Metabolic Diseases: Lessons from Mouse Models

Abstract: Forkhead box O (FOXO) transcription factors have been implicated in regulating the metabolism, cellular proliferation, stress resistance, apoptosis, and longevity. Through the insulin receptor substrate ? phosphoinositide 3-kinase ? Akt signal cascade, FOXO integrates insulin action with the systemic nutrient and energy homeostasis. Activation of FOXO1 in liver induces gluconeogenesis via phosphoenolpyruvate carboxykinase (PEPCK)=glucose 6-phosphate pathway, and disrupts mitochondrial metabolism and lipid meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
168
3
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(183 citation statements)
references
References 127 publications
10
168
3
2
Order By: Relevance
“…Based on our data, combined with that of previous reports [33,34], we propose a model for the mechanism of FOXQ1 action on hepatic gluconeogenesis (Fig. 8).…”
Section: Resultssupporting
confidence: 77%
“…Based on our data, combined with that of previous reports [33,34], we propose a model for the mechanism of FOXQ1 action on hepatic gluconeogenesis (Fig. 8).…”
Section: Resultssupporting
confidence: 77%
“…After transfecting the effective siSOCS3 into the hepatocytes of IUGR rats, insulin sensitivity was restored and demonstrated a significantly greater downregulation in the transcriptional expressions of G6Pase and PEPCK than those without siSOCS3 treatment. Furthermore, phosphorylated Akt2 levels in CG-IUGR liver cells were elevated after transfection, and subsequently forkhead box O1 was inactivated by phosphorylation to inhibit the transcription of G6Pase and PEPCK (31). Therefore, we confirmed that knocking down the expression of SOCS3 ameliorates the insulin signaling pathway and decreases hepatic glucose production by downregulating the transcriptional expressions of gluconeogenesis genes in primary hepatocytes of CG-IUGR rats.…”
Section: Articlessupporting
confidence: 62%
“…This factor is known to control expression of the enzymes phosphoenolpyruvate carboxykinase (PEPCK) and glucose-6-phosphatase (G6Pase) in the liver, both regulatory enzymes of gluconeogenesis. 21 Consistent with changes in FoxO1, both PEPCK and G6Pase were increased in liver of obB2KO mice. Conversely, intraportal injection of BK in lean mice acutely decreased FoxO1 and PEPCK mRNA expression in the liver.…”
mentioning
confidence: 60%
“…G6Pase and PEPCK are important regulatory enzymes for activation of the gluconeogenesis pathway and both enzymes are transcriptionally controlled by FoxO1. 21 The 25-hydroxycholesterol 7-alpha-hydroxylase (CYP7b1) expression is dramatically decreased. Additionally, we found a decrease in the expression of glucokinase (GCK) mRNA in obB2KO.…”
Section: Expression Of Gluconeogenesis Regulatory Enzymes Is Increasementioning
confidence: 99%